The bad habit of individualistic religion (Acta Theologica)
Because of an interpersonal world view, Ubuntu provides a much-needed reference point for navigating contentious issues for both political and spiritual discourse. The intent, in this instance, is not so much a polemic against political individualism as it is a reckoning with how Christian spirituality per se matters in the academy and public spheres. The concept of “Ubuntu” complements Christian spirituality in that the conceptualisation of Ubuntu moves us beyond notions of soteriology based in individualism and vapid understandings of personal salvation. In turn, Ubuntu expands the understanding of communal spirituality, by providing the reader better insight into the deepening paradox in which, by focusing upon community, one gains a deeper significance of self.